The impact of stuttering in the university. (30th September 2022) - Azios, Michael; Stamatis, Maria; De Nardo, Thales; Tetnowski, John
Abstract : Objective: The aims of this investigation were to explore (a) the experiences of women who stutter in university settings; (b) the impact of stuttering related to the emotions attached to stuttering; (c) the impact of stuttering on relationships for women; and (d) coping and management of stuttering within the university setting. Method: Interpretive phenomenological analysis was used to understand the lived experiences of women who stutter when attending university. In-depth semi-structured interviews were collected from seven women who stutter and subjected to inductive analysis. Results: Qualitative data analysis indicated that participants reported four themes related to their university experiences: 'Role of support'; 'Client-centered therapy'; 'Role of authoritative figures'; and 'The stuttering stereotype exists.' Discussion: Women are presented with unique challenges while attending university, as they must combat stereotypes related to stuttering and being a woman, and they must also overcome the related obstacles. Conclusions: There is much work to be done in the university setting, in order to change how people who stutter are portrayed and how stuttering is perceived. These data point toward the need for advocacy training within the university setting, and for more holistic approaches to be utilized in stuttering intervention.